SOCIAL ADAPTATION OF CHILDREN TO PRESCHOOL EDUCATIONAL ORGANIZATIONS (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the process of social adaptation of children to preschool educational organizations, emphasizing its significance for their emotional, cognitive, and communicative development. The study examines key factors influencing adaptation, such as family involvement, peer interactions, teacher-child relationships, and the educational environment. Special attention is given to the role of play-based learning and gradual integration strategies in fostering a smooth transition from home to preschool. The findings highlight the importance of creating a supportive and inclusive atmosphere that meets children’s individual needs, promotes positive socialization, and lays a strong foundation for future academic success.